Reversible Immunoaffinity Interface Enables Dynamic Manipulation of Trapping Force for Accumulated Capture and Efficient Release of Circulating Rare Cells. Issue 20 (2nd September 2021) - Chen, Xiaofeng; Ding, Hongming; Zhang, Dongdong; Zhao, Kaifeng; Gao, Jiafeng; Lin, Bingqian; Huang, Chen; Song, Yanling; Zhao, Gang; Ma, Yuqiang; Wu, Lingling; Yang, Chaoyong
Abstract: Controllable assembly and disassembly of recognition interface are vital for bioanalysis. Herein, a strategy of dynamic manipulation of trapping force by engineering a dynamic and reversible immunoaffinity microinterface (DynarFace) in a herringbone chip (DynarFace‐Chip) for liquid biopsy is proposed. The DynarFace is assembled by magnetically attracting immunomagnetic beads (IMBs) on chip substrate, with merits of convenient operation and reversible assembly. The DynarFace allows accumulating attachment of IMBs on circulating rare cell (CRC) surfaces during hydrodynamically enhanced interface collision, where accumulatively enhanced magnetic trapping force improves capture efficiency toward CRCs with medium expression of biomarkers from blood samples by 134.81% compared with traditional non‐dynamic interfaces. Moreover, magnet withdrawing‐induced disappearance of trapping force affords DynarFace disassembly and CRC release with high efficiency (>98%) and high viability (≈98%), compatible with downstream in vitro culture and gene analysis of CRCs. This DynarFace strategy opens a new avenue to accumulated capture and reversible release of CRCs, holding great potential for liquid biopsy‐based precision medicine. Abstract : A dynamic and reversible immunoaffinity microinterface is engineered in a microfluidic chip, with merits of easy operation and reversible assembly. It enables dynamic manipulation of trapping force for accumulated capture and reversible release of circulating rare cells, holding great potential in liquid biopsy‐based precision medicine.